2007
DOI: 10.1111/j.1468-3083.2006.02116.x
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of eccrine poroma on a burn site

Abstract: References1 Martin L, Piette F, Blanc P et al. Clinical variants of the preprotuberant stage of dermatofibrosarcoma protuberans. Br J Dermatol 2005; 153: 932-936.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…For the intradermal poroma, that is, dermal duct tumor, no epidermal connection is present . In one of the largest case series of eccrine poromas (45 cases), 16% of the poromas studied arose in areas with antecedent trauma, and since then, eccrine poromas have been described occurring in the setting of electron beam therapy, burn sites, and chronic radiation dermatitis . Documentation in the literature of eccrine poromas arising in lymphedema is sparse to none, although Lynch et al reported a case of porocarcinoma arising in the setting of breast cancer‐related lymphedema …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the intradermal poroma, that is, dermal duct tumor, no epidermal connection is present . In one of the largest case series of eccrine poromas (45 cases), 16% of the poromas studied arose in areas with antecedent trauma, and since then, eccrine poromas have been described occurring in the setting of electron beam therapy, burn sites, and chronic radiation dermatitis . Documentation in the literature of eccrine poromas arising in lymphedema is sparse to none, although Lynch et al reported a case of porocarcinoma arising in the setting of breast cancer‐related lymphedema …”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the clinical and histologic features of ESFAs overlap with those of eccrine poromas to such an extent that rather than classifying ESFA as a separate entity distinct from poroma, it may be more prudent to consider ESFA as an entity belonging along the continuum of eccrine poroid proliferations, with poroma being associated with a tumorigenic growth pattern and an abundant neoplastic epithelial component while ESFA represents a more typically reactive, reticular proliferation with a robust stromal component. Eccrine proliferations arising in the setting of lymphedema and other reactive settings have been more often classified as ESFAs, although eccrine poromas have been described to occur in similar reactive settings as well . The commonalities between eccrine poromas and ESFAs extend to additional shared features, including benign prognosis, rare incidence of malignant transformation, and indolent biologic behavior that obviates the need for aggressive treatment modalities .…”
Section: Discussionmentioning
confidence: 99%
“…They also occasionally present as pigmented lesions, mimicking pigmented basal cell carcinomas . They have also been reported at the site of a burn or scar . Several cases of poromatosis have been reported during pregnancy, suggesting a possible hormonal trigger.…”
Section: Discussionmentioning
confidence: 99%
“…Burn scar neoplasia is well described, with hundreds of case reports in humans 18 and a few in domestic animals 19,20 . In humans, squamous cell carcinoma is the most common burn scar neoplasm, although benign neoplasia, such as eccrine poroma, can develop 17 . Factors that make a burn scar more likely to produce neoplasia include healing by second intention, nonhealing wounds and ulceration 18 .…”
Section: Discussionmentioning
confidence: 99%